2006
DOI: 10.1097/qad.0b013e328010238d
|View full text |Cite
|
Sign up to set email alerts
|

Impact of suppressive herpes therapy on genital HIV-1 RNA among women taking antiretroviral therapy: a randomized controlled trial

Abstract: HSV-2 facilitates residual genital HIV-1 replication among dually infected women taking HAART despite HIV-1 suppression at the systemic level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 30 publications
5
65
1
4
Order By: Relevance
“…We also found that women randomized to valacyclovir had a lower risk of genital HSV DNA shedding, consistent with previous studies [41,42]. In contrast, we did not detect a significant association between valacyclovir and cervical HIV-1 RNA levels or shedding, which is consistent with results from a cohort receiving HAART reported by Ouedraogo et al [43] and an antiretroviral-naive cohort reported by Delany et al [17] but in conflict with 3 other randomized trials conducted in antiretroviral-naive cohorts [12][13][14]. One potential explanation for the lack of association in our study is that a high proportion (.40%) of women in our cohort were not shedding HIV-1 in cervical secretions and had low baseline cervical HIV-1 RNA levels after initiation of ZDV, which reduces cervical HIV-1 RNA levels by 1 log 10 copies/mL after 1 week of ZDV treatment [44].…”
Section: Discussionsupporting
confidence: 92%
“…We also found that women randomized to valacyclovir had a lower risk of genital HSV DNA shedding, consistent with previous studies [41,42]. In contrast, we did not detect a significant association between valacyclovir and cervical HIV-1 RNA levels or shedding, which is consistent with results from a cohort receiving HAART reported by Ouedraogo et al [43] and an antiretroviral-naive cohort reported by Delany et al [17] but in conflict with 3 other randomized trials conducted in antiretroviral-naive cohorts [12][13][14]. One potential explanation for the lack of association in our study is that a high proportion (.40%) of women in our cohort were not shedding HIV-1 in cervical secretions and had low baseline cervical HIV-1 RNA levels after initiation of ZDV, which reduces cervical HIV-1 RNA levels by 1 log 10 copies/mL after 1 week of ZDV treatment [44].…”
Section: Discussionsupporting
confidence: 92%
“…erpes simplex virus 2 (HSV-2) is one of the most common causes of genital ulcer disease worldwide and epidemiological studies consistently demonstrate a strong link between HSV-2 and the risk for HIV acquisition and transmission (1)(2)(3). The prevalence of HSV-2 infection among people with HIV from sub-Saharan African countries ranges from 50 to 90% (4).…”
mentioning
confidence: 99%
“…Interestingly HIV transmission in the WITS case-control study was not associated with the presence of HSV DNA either but the numberswere probablytoo small to determine this 17 . Althoughsuppressive therapy with valaciclovir for 12 weeks was associated with a decrease in the frequency of detection of HSV DNA this had no impact on the frequency of detection or load of HIV-1 in the genital tract in women taking HAART 19 , whereas the same treatment in women not taking HAART was associated with a reduction in both genital tract and plasma HIV-1 viraemia 20 .…”
Section: Subsequently In Vitromentioning
confidence: 95%